Influence of massmedia on public opinion during the kovid virus pandemic 19 (Heritage, 2021)
Epidemicsthroughout human history have beenan integral part of the struggleof man with the negative impactof the environment, but also a factorthatchanged the courseofdevelopmentofcivilization. The consequenceswerefar-reaching, but with the progressofsocietyandscience as a wholeand the gradual creationofimmunity, the effectofepidemicswaslessandlessthreatening to the survivalof the human species. The complexityof human societyin the conditionsof a pandemicnecessarilyviolatestraditionalvalues ​​andrelationsbetweenindividuals, socialandpolitical groups. The devastatingimpactcausedby the pandemicwas used bypoliticalgroupsandindividuals to achieve personalgoals, but theirownprejudices, abusing the massmedia. With the massappearanceofmisinformation (infodemia), the fightagainst the suppressionof the pandemic is directlyendangered, but also the confusionthat has gripped the population. The socialandpoliticalproblemswefacedbefore the pandemicnowawait us intheirextremeform, because the resources to solvethemarealmostexhausted.
Keywords: pandemic, massmedia, infodemia, politicalstruggle, psycho - physicalhealth